IMPLEMENTASI KEBIJAKAN RETRIBUSI PASAR TRADISIONAL HIGIENIS BAHARI BERKESAN KOTA TERNATE - IFANDRI, PRIMA; KALANGI, JOHNY; RUMAWAS, WEHELMINA (Sam Ratulangi University, 2016)
Abstrack : Regional retribution are levies other than taxes levied by local governments depending on the ability to provide services to the public. One of the retribution of local government retribution is traditional market retribution. Traditional market retribution constitute a payment for the provision of traditional / simple market facilities in the form of a court location or store that are provided or managed by the local government for the benefit and can be enjoyed by a particular community or entity.Ternate City government, North Maluku Province is currently focusing on the development of goods and services sector. One of the efforts of the Ternate City government to encourage the improvement of trade and services sector is to build traditional markets. One of these markets is bahari berkesan traditional hygienic market.The problem that arises is often a conflict between officers and traders. Many traders are allowed to sell not in accordance with the places that have been determined to make the market look neatly organized and create congestion. Slow settlement of infrastructure issues related to the comfort of the traders and the buyers.The research method used in this study is a qualitative research method that aims to get more in depth information about how Implementation of Bahari Berkesan Traditional Hygienic Market Retribution Policy in Ternate City. Informants in this study as many as 9 informants. The results showed that the factors that play an important role in Implementation of Bahari Berkesan Traditional Hygienic Market Retribution Policy in Ternate City is communication, resources, attitude, and bureaucratic structure.Kata Kunci : Implementation of the policy, retribution